Extraction of Palladium from Nitrate Medium by Emulsion Liquid Membrane Containing CYANEX 471X as Carrier. Issue 2 (23rd February 2017) - Kassem, A. T.; Masry, B. A.; Zeid, M. M.; Noweir, H. G.; Saad, E. A.; Daoud, J. A.
ABSTRACT: Extraction of Pd(II) from nitric acid solution with CYANEX 471X in chloroform was carried out using liquid–liquid extraction and emulsion liquid membrane (ELM) techniques. Extraction equilibrium was postulated using the slope analysis method. KSCN solution efficiently stripped Pd(II). In the ELM investigations, the effects of the different parameters affecting the membrane stability were studied. The prepared membrane was found to be selective for Pd(II) extraction in the presence of some interfering ions and its permeation reached 98%. The kinetics of Pd(II) permeation through the prepared membrane indicated that the rate of permeation depends on the carrier, Pd(II), and nitric acid concentration.